INFORMATION EXPROSURE VIA PUBLIC INFORMATION MEDIA ONLINE AND THE IMAGE OF BANGKOKTHONBURI UNIVERSITY FROM THE PERSPECTIVE OF BANGKOKTHONBURI UNIVERSITY STUDENTS - Buranadechachai, Sukanya; Kaweejarukorn, Kittiya; Rojanasrangsakul, Napaket (Journal of MCU Nakhondhat, 2023)
The objectives of this research were to study 1) the public relations exposure through online media of Bangkokthonburi University in the perspective of students. 2) the image of Bangkok Thonburi University in the perspective of students. And 3) the relationship between the image of Bangkokthonburi University and exposure to online public relations. Is a quantitative research survey research type with sample consisted of 396 members. Using Multi-sampling random. Data were analyzed using percentage, mean, standard deviation and Pearson’s correlation. The results found: 1) There is an exposure to press releases via online media of Bangkok Thonburi University on the Facebook page of Bangkok Thonburi University. at the highest level ( = 4.62). 2) The feeling towards the overall image of Bangkok Thonburi University was at a very good level ( = 4.57). And 3) The overall image of Bangkokthonburi University had a positive correlation with perception of online public relations at a high level (r = .600), with a statistical significance of .01. Reflecting that when media has changed to online media or new media more therefore allowing access to use anywhere, anytime without borders. As a result, it can be easily exposed to the media according to the wishes of the recipients. Exposure to the media in this unlimited time and place results in a good image for the organization in a relatable way. The good image of the organization is the result of the organization that has used the media to promote the organization continuously.